A device for characterising the mechanical properties of the plantar soft tissue of the foot. Issue 11 (November 2015) - Parker, D.; Cooper, G.; Pearson, S.; Crofts, G.; Howard, D.; Busby, P.; Nester, C.
Highlights: We developed a device to characterise the plantar soft tissue. We present a method for isolating tissue specific response under bulk compression. The device was shown to be suitably accurate, with high validity and low variability. Tissue characterisation was demonstrated at rates equivalent to gait. Abstract: The plantar soft tissue is a highly functional viscoelastic structure involved in transferring load to the human body during walking. A Soft Tissue Response Imaging Device was developed to apply a vertical compression to the plantar soft tissue whilst measuring the mechanical response via a combined load cell and ultrasound imaging arrangement. Accuracy of motion compared to input profiles; validation of the response measured for standard materials in compression; variability of force and displacement measures for consecutive compressive cycles; and implementation in vivo with five healthy participants. Static displacement displayed average error of 0.04 mm (range of 15 mm), and static load displayed average error of 0.15 N (range of 250 N). Validation tests showed acceptable agreement compared to a Houndsfield tensometer for both displacement (CMC > 0.99 RMSE > 0.18 mm) and load (CMC > 0.95 RMSE < 4.86 N). Device motion was highly repeatable for bench-top tests (ICC = 0.99) and participant trials (CMC = 1.00). Soft tissue response was found repeatable for intra (CMC > 0.98) and inter trials (CMC > 0.70). The device has been shown to be capable of implementing complex loading patterns similar to gait, and of capturing the compressive response of the plantar soft tissue for a range of loading conditions in vivo.